Effect of blood oxidative stress indicators on oral mucositis in patients undergoing radiotherapy for nasopharyngeal carcinoma - HongXia Pang; SuZhen Li; XiaoYi Fu; ShaoMin Wen; DanYu Chen; XiaoChun Sun; Yong Chen; Song Yang (European Journal of Medical Research)
Abstract Objectives To investigate the correlation of total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-PX), and advanced oxidized protein product (AOPP) levels in the progression of oral mucositis (OM) during nasopharyngeal carcinoma (NPC) radiotherapy. Methods This prospective study included 102 patients diagnosed with NPC and eligible for radiotherapy indications. T-AOC, GSH-PX, and AOPP were measured before treatment (T0) and during the second week (T1), fourth week (T2), and sixth week (T3) of the intensity-modulated radiation therapy (IMRT) period. Patients were categorized into severe OM (SOM) (n = 21) and Non-SOM (n = 81) groups at week 6. Serum T-AOC, GSH-PX, and AOPP levels were compared at different time periods. The trends of these markers in the two groups during the course of treatment were analyzed. Finally, stepwise logistic regression was conducted to analyze the risk factors for SOM in NPC patients undergoing IMRT. Results At T1 and T2 of IMRT, T-AOC and GSH-PX were higher in the SOM group than in the Non-SOM group; At T3, T-AOC and GSH-PX were lower in the SOM group than in the Non-SOM group. T-AOC and GSH-PX had similar change trends in Non-SOM or SOM patients, i.e., T-AOC levels continued to increase at T2 and decreased at T3, and GSH-PX increased significantly at T2 and decreased at T3. Of interest was the fact that T-AOC and GSH-PX decreased significantly more in SOM patients than in Non-SOM patients at T3, and that AOPP levels were in a constant state of increase in SOM patients. Preoperative hypoproteinemia, the absence of oral mucosal protective agents, and the receipt of synchronous chemotherapy were independent risk factors for increasing the course of OM in patients with NPC. Conclusions NPC patients undergoing IMRT exhibit dynamic alterations in blood T-AOC, GSH-PX, and AOPP. Notably, the persistent elevation of these biomarkers, particularly AOPP, is significantly associated with the progression of SOM in these patients. These findings underscore the involvement of oxidative stress imbalance in the pathogenesis of oral mucositis following IMRT.